Burden of proof [large type] - Bunn, T. Davis, 1952- (Center Point Large Print, 2021)
Adrian was murdered on the steps of the courthouse in Jacksonville, Florida. Ever since that day his brother Ethan has sensed a deep disconnect between the man he should have been and the one he has become. His days play out a beat too slow, his mind replaying the scene of his failure to save his brother. Then Adrian's widow asks for his help in uncovering what was really behind Adrian's death. Ethan is stunned to learn that she and her late husband were involved in a case that threatens the global power structure. As Ethan joins the search for answers, he will enter into his own past-- and discover a means of redeeming his future. -- adapted from back cover